Analysis of The Professional Development Program of General Foundation Course Teachers In Higher Vocational Colleges in China:Basis for The Teacher Professional Development Framework - Wang, Huiling (Pacific International Journal, 2024)
Higher vocational education in China plays a vital role in national economic development by preparing a skilled workforce. General Foundation Courses (GFC) are crucial in this system, providing essential skills in mathematics, language, and basic sciences, yet they often receive less attention and fewer resources compared to specialized courses. This disparity leads to outdated teaching methods and insufficient professional development for GFC teachers. Professional Development Programs (PDPs) aim to address these issues, but their effectiveness needs thorough evaluation. This study assesses the current state of PDPs for GFC teachers in China's higher vocational colleges, identifying challenges and proposing a comprehensive framework for improvement. Using qualitative research methods, including semi-structured interviews with 12 GFC teachers and document analysis, the study highlights the importance of institutional support, relevance of training programs, and continuous professional development. Findings suggest that increased resources, customized PDPs, and ongoing professional growth opportunities are crucial for enhancing teaching practices and student outcomes. The study's implications underscore the need for policymakers and educational administrators to prioritize resource allocation, design tailored PDPs, and promote continuous learning to improve the quality of vocational education and contribute valuable insights to the literature on teacher professional development.